Exploration and Construction of Personalized Customization Mode in Modern Fashion Design - Sun Huaiqun (SHS Web of Conferences)
With the diversification of consumer demands and the enhancement of personalized service awareness, the modern fashion design field is ushering in a new development opportunity centered on personalized customization. At the same time, the digital transformation of the fashion industry and the widespread application of intelligent technology provide strong support for the implementation of personalized customization models. This article takes the theoretical basis of personalized customization as the starting point, and combines the theories of flexible production, user experience, and digital technology to deeply explore how the field of fashion design can achieve synchronous improvement of consumer participation and product differentiation through data-driven demand mining, intelligent design processes, and flexible production technology. The article focuses on constructing a personalized customization implementation path based on big data analysis, artificial intelligence algorithms, and online interaction platforms, covering key links such as demand analysis, virtual fitting, and on-demand production. By analyzing the advantages of this model in meeting personalized consumer needs, improving production efficiency, and promoting green design and sustainable development, this article further proposes specific suggestions for technology optimization, process simplification, and user experience improvement. Research has shown that the widespread application of personalized customization models will become an important lever for the modern clothing industry to build competitive advantages and promote industrial upgrading, while also providing new development directions and reference frameworks for future clothing design and production models.